Integrated genomics with refined cell-of-origin subtyping distinguishes subtype-specific mechanisms of treatment resistance and relapse in diffuse large B-cell lymphoma - Janek S. Walker; Kerstin Wenzl; Joseph P. Novak; Matthew E. Stokes; Melissa A. Hopper; Abigail R. Dropik; Miranda S. Siminski; Allison M. Bock; Vivekananda Sarangi; Maria Ortiz; Nicholas Stong; C. Chris Huang; et al. (Blood Cancer Journal)
Abstract Up to 40% of diffuse large B-cell lymphoma (DLBCL) patients do not experience a durable response to frontline immunochemotherapy, and prospective identification of high-risk cases that may benefit from personalized therapeutic management remains an unmet need. Molecular phenotyping techniques have established a landscape of genomic variants in diagnostic DLBCL; however, these have not yet been applied in large-scale studies of relapsed/refractory DLBCL, resulting in incomplete characterization of mechanisms driving tumor progression and treatment resistance. Here, we performed an integrated multiomic analysis on 228 relapsed/refractory DLBCL samples, including 24 with serial biopsies. Refined cell-of-origin subtyping identified patients harboring GCB and DZsig+ relapsed/refractory tumors in cases with primary refractory disease with remarkably poor outcomes, and comparative analysis of genomic features between relapsed and diagnostic samples identified subtype-specific mechanisms of therapeutic resistance driven by frequent alteration to MYC, BCL2, BCL6, and TP53 among additional strong lymphoma driver genes. Tumor evolution dynamics suggest innate mechanisms of chemoresistance are present in many DLBCL tumors at diagnosis, and that relapsed/refractory tumors are primarily comprised of a homogenous clonal expansion with reduced tumor microenvironment activity. Adaptation of personalized therapeutic strategies targeting DLBCL subtype-specific resistance mechanisms should be considered to benefit these high-risk populations.